Supervised and Semi-Supervised Text Mining Models for Hotel Reviews Analysis (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Online reviews have great impact on today’s business and commerce. Decision making for purchase of online products mostly depends on reviews given by the users. Hence, opportunistic individuals or groups try to manipulate product reviews for their own interests. This paper introduces some semi-supervised and supervised text mining models to detect fake online reviews as well as compares the efficiency of both techniques on dataset containing hotel reviews.